Insights from a State Islamic University on Arabic Education as a Catalyst for Religious Moderation in Indonesia - Yasmadi, Yasmadi; Husna, Ilya; Arsya, Fajriyani; Rahmah, Azizah; Kustati, Martin; Perrodin, David D. (Universitas Negeri Makassar, 2024)
This research aims to investigate the integration of religious moderation in Arabic language learning at a state Islamic university. Employing a qualitative descriptive method, data was gathered through observation, in-depth interviews, and documentation. The study emphasizes a tourism-based approach that incorporates local wisdom and pluralism into the Kalam course, aimed at enhancing students' Arabic communication skills. The findings indicate that embedding religious moderation within the Arabic curriculum promotes tolerance, inclusivity, and a moderate outlook among students, which, in turn, contributes to social and religious harmony in Indonesia. Additionally, the research highlights the importance of local cultural contexts in shaping student behavior. The study suggests further exploration of internal and external factors that influence the implementation of religious moderation in Arabic education at a state Islamic university. It also recommends adopting a mixed-method approach in future research to gain a deeper understanding of these dynamics and enhance the effectiveness of religious moderation efforts.